Quantum computation and logic : how quantum computers have inspired logical investigations /: how quantum computers have inspired logical investigations. ([2018]) - Dalla Chiara, Maria Luisa, 1938-; Giuntini, Roberto; Leporini, Roberto; Sergioli, Giuseppe
No abstract available